Identifying gaps on health impacts, exposures, and vulnerabilities to climate change on human health and wellbeing in South America: a scoping review - Palmeiro-Silva, Yasna K.; Lescano, Andrés G.; Flores, Elaine C.; E, Yamileth Astorga; Rojas, Luis; Chavez-Hermosilla, Mario; Mora-Rivera, Wendel; Hartinger, Stella M. (The Lancet Regional Health - Americas, 2023)
There is an important gap in regional information on climate change and health, limiting the development of science-based climate policies in South American countries. This study aims to identify the main gaps in the existing scientific literature on the impacts, exposure, and vulnerabilities of climate change on population health. A scoping review was performed guided by four sub-questions focused on the impacts of climate change on physical and mental health, exposure and vulnerability factors of population to climate hazards. The main findings showed that physical impacts mainly included infectious diseases, while mental health impacts included trauma, depression, and anxiety. Evidence on population exposure to climate hazards is limited, and social determinants of health and individual factors were identified as vulnerability factors. Overall, evidence on the intersection between climate change and health is limited in South America and has been generated in silos, with limited transdisciplinary research. More formal and systematic information should be generated to inform public policy.None.
openalex: W4386122878 KerkoCite.ItemAlsoKnownAs: 10.1016/j.lana.2023.100580 2129771:34CUXJBZ 5072953:9I4GQHIZ
Keywords: openalex:citedBy; openalex:import; selected_for:effects of climate ch...on learning...LMICs 2024; tagged